2021
DOI: 10.1091/mbc.e20-09-0576
|View full text |Cite
|
Sign up to set email alerts
|

Septins and a formin have distinct functions in anaphase chiral cortical rotation in theCaenorhabditis eleganszygote

Abstract: Many cells and tissues exhibit chirality that stems from the chirality of proteins and polymers. In the C. elegans zygote actomyosin contractility drives chiral rotation of the entire cortex circumferentially around the division plane during anaphase. How contractility is translated to cell-scale chirality, and what dictates handedness, are unknown. Septins are candidate contributors to cell-scale chirality because they anchor and crosslink the actomyosin cytoskeleton. We report that septins are required for a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 53 publications
2
7
0
Order By: Relevance
“…S6 B and Movie S10 ) indicating that NMY-2/Myosin activity in the AB cell drives both a whole-cell and whole-embryo rotation. Together, this shows that the whole embryo is essentially free to rotate inside the eggshell, consistent with earlier observations ( 47 , 48 , 60 , 61 ).…”
Section: Resultssupporting
confidence: 92%
“…S6 B and Movie S10 ) indicating that NMY-2/Myosin activity in the AB cell drives both a whole-cell and whole-embryo rotation. Together, this shows that the whole embryo is essentially free to rotate inside the eggshell, consistent with earlier observations ( 47 , 48 , 60 , 61 ).…”
Section: Resultssupporting
confidence: 92%
“…Intriguingly, α-Actinin, IQGAP, and unconventional myosins also induce directional actin filament movements such as counterclockwise swirling. This actin-dependent cell chirality is observed in a wide range of animals from Drosophila to mammals 57 , 111 , 114 121 . While much of the evidence for actin bending and its biological consequences to date comes from studies using in vitro systems, recent studies using cells and model organisms revealed that cell chirality has important roles in processes such as cell migration and L-R asymmetric organ development 97 , 106 , 122 , 123 .…”
Section: Discussionmentioning
confidence: 88%
“…These strains are considered to be loss‐of‐function alleles due to the corresponding mRNA being undetectable by northern blotting, and protein undetectable by immunoblotting (Nguyen et al, 2000). We recently published that our strain bearing unc‐59(e1005) no longer contains Gly29‐to‐Arg29 but instead contains a different residue mutation (Gly54‐to‐Arg54; Zaatri et al, 2021), which disrupts the 5′ splice site consensus sequence (Riddle et al, 1997) in the intron between exon 1 and exon 2 of unc‐59 . While unc‐59(e1005) allele bearing Gly29‐to‐Arg29 and the unc‐61(e228) allele were previously reported to have postembryonic defects consistent with roles germline function, we wanted to validate and perform a detailed characterization of our unc‐59(e1005) allele bearing Gly54‐to‐Arg54.…”
Section: Resultsmentioning
confidence: 99%